2019
DOI: 10.1038/s41598-019-49462-w
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant gut microbiota markers for the classification of obesity-related metabolic abnormalities

Abstract: The gut microbiota (GM) is related to obesity and other metabolic diseases. To detect GM markers for obesity in patients with different metabolic abnormalities and investigate their relationships with clinical indicators, 1,914 Chinese adults were enrolled for 16S rRNA gene sequencing in this retrospective study. Based on GM composition, Random forest classifiers were constructed to screen the obesity patients with (Group OA) or without metabolic diseases (Group O) from healthy individuals (Group H), and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
175
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(219 citation statements)
references
References 50 publications
25
175
0
1
Order By: Relevance
“…The OMS patients had the highest bacterial diversity, followed by O and NW patients. This observation is in agreement with other studies with big cohorts of obese patients that also observe an increase in diversity in them [26]. Contrary, some studies revealed a decrease in diversity in obese patients [27,28].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The OMS patients had the highest bacterial diversity, followed by O and NW patients. This observation is in agreement with other studies with big cohorts of obese patients that also observe an increase in diversity in them [26]. Contrary, some studies revealed a decrease in diversity in obese patients [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…The PCoA analysis of the microbiota showed that the most compact cluster was formed among the NW samples, while the most disperse was the OMS group; the O group seemed to be an intermediate state of healthy and obese with metabolic syndrome. Similar clustering behavior was recently observed as a consequence of metabolic abnormalities in the adult population [26].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, a signi cant increase of Roseburia was only detected in FHFD, which was positively correlated with weight gain and NAS score in female rats, but not in males. As a butyrate-producing bacterium, Roseburia was reported to be negatively correlated with body weight and serum lipids in Chinese adults 35 . A previous study indicated that restoring of Roseburia spp.…”
Section: Discussionmentioning
confidence: 99%